Examining the antecedents of medical tourists use of social media from the standpoint of self-efficacy - Balouchi, Mina; Aziz, Yuhanis Abdul (Emerald, 2023)
The purpose of this research is to examine, from the self-efficacy standpoint, the factors that influence medical tourists' use of social media for travel planning. To that end, this study presents a conceptual framework for evaluating medical tourists' online behaviour and empirically tests the model's validity by examining various dimensions of self-efficacy.A sample of 224 people who searched for medical tourism information online was used in this study. Partial least squares structural equation modelling (PLS-SEM) was employed to test the proposed model with data from an online questionnaire survey.The findings suggest that sources of self-efficacy reinforce one's belief in the ability to use social media for medical travel planning purposes. According to the structural model analysis results, with the exception of social persuasion (SP), all of the proposed factors were significant sources of self-efficacy.The findings can assist medical tourism providers in optimising online searches for medical travel information, as well as medical tourism destination marketers in directing the tourism providers' marketing efforts towards the use of social media to target potential medical tourists more efficiently and on a larger scale.This study is being conducted in response to a significant knowledge gap in identifying the factors that influence medical tourists' online behaviour. This information can help medical tourism destination marketers gain a competitive advantage by using social media to target potential medical tourists more effectively and on a larger scale.